Effects of Zinc Oxide nanoparticles on Streptococcus pyogenes - Liang, Sharolynne, Xiao Tong; Wong*, Ling Shing; Lim, Yang Mooi; Lee, Poh Foong; Sinouvassane, Djearamane (Elsevier, 2020)
Zinc oxide nanoparticles (ZnO NPs) have been used in the treatment of bacterial infections due to their antibacterial properties. The present study was aimed to explore the antibacterial effects of ZnO NPs on Streptococcus pyogenes. The antibacterial properties were evaluated by investigating the growth inhibition and oxidative stress effects of ZnO NPs on S. pyogenes. The bacterial growth inhibition was determined through the percentage of reduction in the turbidity of bacterial suspension and bacterial colony upon treating with ZnO NPs, while the oxidative stress of ZnO NPs on bacterial cells were assessed by measuring the levels of reactive oxygen species (ROS) and lipid peroxidation. The results showed the dose dependent and significant (p < 0.05) growth inhibition and oxidative stress effects on S. pyogenes for 10 to 100 μg/mL ZnO NPs at 24 h. Fourier-transform infrared spectrometry (FTIR) analysis confirmed the binding of ZnO NPs to polypeptides and glycogen from the bacterial cell wall. Further, the scanning electron microscopy (SEM) results showed the attachment of ZnO NPs to bacterial cell wall and the resultant cell wall disruption and cell damage. The study results confirmed the antimicrobial effects of ZnO NPs on S. pyogenes.